PERANCANGAN SISTEM INFORMASI RADIOLOGI RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH DR. RUBINI MEMPAWAH - Eiswanda, Angga (Jurusan Informatika Universitas Tanjungpura, 2013)
The hospital is a health care institution is acomplex, dense and capital-intensive profession. Thiscomplexity arises because of hospital services on arange of service delivery, education and research, andincludes a variety of measures and medicaldisciplines. So that the hospital is able to perform complex functions such, the hospital must have aprofessional human resources both in the technicalfield of medical and health administration. Outpatientservices is one unit of work in the scope of hospitalserving outpatient treatment and not more than 24hours of service. Development of hospital outpatientinfluenced by the development of advanced medicaltechnology that provides a variety of services,including radiation and chemotherapy centers,diagnostic imaging centers, rehabilitation centers,hospitalization pasial, sports medicine clinics,women's health clinics, occupational health andothers. One type of medical support services in ahospital radiology service that is performed by aradiology unit installation. Installation is the venuefor the radiology radiology services to patients in needwith rapid diagnosis and precise or accurateradiotherapy delivery. Many radiology departmentthat became a symbol of pride for each hospital,because of the high-tech services which is an effectivemarketing tool in attracting doctors or patients and installation procedures in radiology is a major source of income.